The influence of the culture of France and Italy on the genre of masque in England - Sokolova, Alla V. (Linguistics and Culture Review, 2021)
The article discusses the ways of interaction of the French court ballet, the Italian carnival, Italian dance and the English court Masque. The features of royal entertainment in France, known since the reign of Henry II, are revealed. The origin of the French court ballet was determined, its socio-political functions aimed at the hierarchical structuring of the royal court, strengthening the authority of the monarch, the unification of the aristocratic nobility and the removal of hotbeds of tension in society were revealed, which were characteristic features for the functional features of the English court Masque. The stages of the origin, formation, heyday, and decline of the French court ballet are described. A parallel is drawn between the burlesque roles of the king in the court ballet and the birth of an antimasque, the founder of which was was B. Johnson, a poet and playwright. It was established that the Italian style coexisted in England with other European styles during the period of the Stuart reign, and Italian dances, costumes, librettos and stage designs were used in the performances of English Masques.